CASH AND LIQUIDITY MANAGEMENT ANALYSIS OF COMPANIES IN IMPROVING PROFITABILITY RATIOS ON THE INDONESIAN STOCK EXCHANGE (IDX) IN THE FOOD & BEVERAGE SUBSECTOR - Pitono, Gerry Nando; Habibburrahman, Habibburrahman (Transpublika Publisher, 2024)
Cash and liquidity management are critical aspects in optimizing the financial performance of a company, especially in the capital market such as the Indonesia Stock Exchange (IDX). This study aims to investigate the impact of cash management and corporate liquidity in improving profitability ratios, with a focus on the Food & Beverage subsector on the IDX. Purposive sampling in this study with multiple linear regression data analysis and descriptive statistics. The findings of this study conclude that profitability is affected by cash management, whereas profitability is not affected by liquidity. Furthermore, the research highlights the importance of efficient cash management practices in maximizing profitability and overall financial health. By effectively managing cash flows and maintaining adequate liquidity levels, companies in the Food & Beverage subsector can improve their financial performance and potentially attract more investors on the IDX. This study provides valuable insights for companies looking to optimize their cash and liquidity management strategies to drive sustainable growth and success in the competitive capital markets of Indonesia.